Virtual reality vs. real world: 3D kinematic analysis in table tennis - Škopek, M.; Hnízdil, J.; Ševcovic, J.; Heidler, J.; Ptácek, M. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction/Purpose This study aims to compare the kinematics of movement during the execution of selected strokes in table tennis in both conventional and virtual reality environments (Michalski at al., 2019). Specifically, it focuses on comparing the motion patterns of players when performing forehand and backhand topspin strokes in regular and virtual settings using 3D motion analysis.